Sistem Pengeloaan Laboratorium SMK Pemesinan di Bandar Lampung - Sugiyanto; Sukmana, Irza; Nafrizal; zulhanif; Saputra, Rizal Adi; Arif, Zainal; Rifaldi, Dwi; Ramadhan, Muhammad Afin (FT Universitas Lampung, 2024)
In the context of vocational education, technicians play a crucial role as partners to teachers in laboratory or workshop settings in schools specializing in machining technology. Despite having received training at their institutions, many technicians lack sufficient competence to optimally support learning activities. This community service initiative aims to enhance the professional competence of technicians in vocational schools through a structured approach. The activity begins with a field study to assess specific needs, followed by the development of a training model that is then reviewed through a Focus Group Discussion (FGD). This training model is designed to provide technicians and laboratory teachers with comprehensive insights into best practices and effective self-development guidelines. The expected outcome is a significant improvement in the competencies of technicians and laboratory teachers in Bandar Lampung.